2018
DOI: 10.1093/cvr/cvy231
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-423-3p exosomes derived from cardiac fibroblasts mediates the cardioprotective effects of ischaemic post-conditioning

Abstract: In conclusion, we demonstrated, for the first time, that CFs participate in cardioprotective effects via an exosomes/microvesicles pathway during the acute phase of ischemia-reperfusion injury and Postcon can enhance this effect by upregulating the expression of CFs exosomes/microvesicles miR-423-3p, which targets the downstream effector RAP2C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 43 publications
2
61
0
Order By: Relevance
“…Accumulating recent evidences reported that microRNA-449, microRNA-423, microRNA-204, and microRNA-665 concentrations were critically altered during H/R-induced cardiomyocyte cell injury. However, H/R-induced H9c2 cells treated with specific inhibition or mimic-miRNAs significantly regulated various cellular inflammatory pathways through their target genes (notch-1, RAP2C, SIRT1, AK1, and Cnr2, respectively) and dramatically reduced oxidative stress, caspase-3 activity, apoptosis, and amazingly protects cardiomyocyte cell injury with obviously increased cellular viability [10,11,25,26]. Very recently, Liang et al research group demonstrated that microRNA-181c-5p expressions were significantly upregulated in hypoxic reoxygentaion-exposed H9c2 cardiomyocytes and rat myocardial ischemia-reperfusion injury (I-RI).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating recent evidences reported that microRNA-449, microRNA-423, microRNA-204, and microRNA-665 concentrations were critically altered during H/R-induced cardiomyocyte cell injury. However, H/R-induced H9c2 cells treated with specific inhibition or mimic-miRNAs significantly regulated various cellular inflammatory pathways through their target genes (notch-1, RAP2C, SIRT1, AK1, and Cnr2, respectively) and dramatically reduced oxidative stress, caspase-3 activity, apoptosis, and amazingly protects cardiomyocyte cell injury with obviously increased cellular viability [10,11,25,26]. Very recently, Liang et al research group demonstrated that microRNA-181c-5p expressions were significantly upregulated in hypoxic reoxygentaion-exposed H9c2 cardiomyocytes and rat myocardial ischemia-reperfusion injury (I-RI).…”
Section: Discussionmentioning
confidence: 99%
“…The increased secretion of extracellular vesicles of trophoblastic origin containing miRNAs into the maternal blood flow due to placental dysfunction in PE can contribute to systemic biological changes. Among the miRNAs circulating in blood plasma, we identified (let-7g-5p, miR-26a-5p, miR-28 (-28-3p, -151a-3p), -30a-5p, -148a-3p, -181 (-181a-5p), -183-5p, -186-5p, -188 (-532-5p), -192-5p, and -320 (-320a), which change their expression in response to oxygen deprivation [18][19][20], oxidative stress (miR-140-3p, -143-3p, -378a-3p) [46], and are associated with immune and inflammatory responses (miR-375) [47], as well as ischemia/reperfusion (miR-423-3p) [48]. In general, our results are consistent with the data of other authors.…”
Section: Discussionmentioning
confidence: 99%
“…As a kind of paracrine factor, MVs allow the transfer of cytoplasmic components such as proteins, mRNAs and miRNAs from one cell to another [8]. However, circulating MVs vary in their components, which varies with the different parent cell types or different stimuli, thus playing different biological roles in occurrence and development of diseases [9,12]. Recent studies have revealed that functional miRNAs can be transferred by MVs and appear to specially home to the site of injury within infarcted myocardium, and MVs were considered as major vector of circulating miRNAs [10].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple experiments have shown that MVs derived from various cell types could play intercellular communication role in diagnostic and therapeutic effects of cardiovascular diseases, mainly by delivering proteins, cytokines and gene messages such as mRNAs and microRNAs (miRNAs) to target cells [8]. Among the components of MVs, miRNAs have been shown to play important roles that regulate the pathophysiological consequences of myocardial I/R injury [9], which can be released from various cells by MVs that protect them from degradation and guarantee their stability and circulation through the blood stream [10], suggesting miRNA in MVs could be a potent therapeutic target and tool for protecting myocardium against I/R injury.…”
Section: Introductionmentioning
confidence: 99%